Experiences of Green Building Professionals With Water‐Related Systems. Issue 8 (1st August 2017) - Chambers, Benjamin D.; Pearce, Annie R.; Edwards, Marc A.; Dymond, Randel L.
Abstract : An internet survey sent to green building professionals explored the level of users' satisfaction with several water‐saving products and methods.